Trends in antimicrobial susceptibility patterns of bacterial isolates in Lahore, Pakistan - Khalid, Nauman; Akbar, Zunaira; Mustafa, Nosheen; Akbar, Jamshaid; Saeed, Shanawar; Saleem, Zikria (Frontiers in Antibiotics, 2023)
Background Antimicrobial resistance (AMR) has provoked a global health issue. Antimicrobial stewardship programs should be implemented to overcome this issue. The aim of this study was to determine the sensitivity patterns of the WHO Access, Watch, Reserve (AWaRe) group of antibiotics that assists in the selection of appropriate empiric antibiotic therapies. Method A descriptive, cross-sectional study was conducted for 6 months, in which 422 culture sensitivity sample reports from the Ghurki Trust Teaching Hospital’s laboratory were obtained through a convenience sampling technique, and the sensitivity patterns of nine offending bacteria to the WHO AWaRe group antibiotics were determined. Descriptive statistics and differences in frequency distribution among the categorical variables were obtained using the Statistical Package for Social Sciences (SPSS) software, version 21. Results Among 422 culture sensitivity sample reports, Escherichia coli (16.1%) was the most common Gram-negative pathogen. Acinetobacter, E. coli, Klebsiella, and Pseudomonas showed 100% sensitivity to polymyxin-b and colistin. Proteus showed the highest sensitivity to meropenem (90%), Staphylococcus aureus showed a 98% sensitivity to linezolid, Staphylococcus epidermidis was 100% sensitive to vancomycin and linezolid, and Streptococcus showed the highest sensitivity to penicillin (100%) and vancomycin (94.7%). Polymyxin b and colistin were found to be the most effective antibiotics against Gram-negative bacteria (100%). Gram-positive bacteria were highly sensitive to linezolid (99.4%), vancomycin (98.2%), chloramphenicol (89.5%), and tigecycline (82.6%). Conclusion Culture sensitivity reports help to rationalize the empirical use of antibiotics in clinical practice in addressing the challenge of antimicrobial resistance. This study showed that polymyxin-b and colistin were the most effective antibiotics against Gram-negative isolates and that Gram-positive bacteria were highly susceptible to linezolid. Updated antibiograms should be used by clinicians to evaluate bacterial susceptibility patterns and rationalize antibiotic empiric therapy.